CNS Complications of Aseptic Meningitis in Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The incidence and outcome of neurological complications occurring during the acute stage of aseptic meningitis in 277 infants under 2 years of age are reported from Johns Hopkins University, Baltimore, and Dartmouth Medical School, Lebanon, NH.